Analysis of the Effect of Monetary Policy on Bank Profitability in Indonesia During the Pandemic - Roni Cahyadi; Eugenia Mardanugraha (International Journal Labs, 2024)
This research aims to analyze the impact of monetary policy on bank profitability in Indonesia during the pandemic using panel data from 93 banks in Indonesia with a time span from 2017-2022 using the Generalized Method of Moments (GMM) approach. The motivation for this research comes from the identification that the relationship between monetary policy and bank profitability is simultaneously very important because it has significant implications in efforts to maintain monetary stability and financial system stability. The research results show that there is a significant positive impact of monetary policy in the form of the BI7DRR policy interest rate on the ROA, ROE and NIM ratios in the 2017-2022 period. Furthermore, the BI7DRR interest rate policy had a significant positive effect on ROA and ROE before and during the pandemic with a greater influence during the pandemic for ROA and during the pre-pandemic period for the ROE ratio. This reflects that banks in Indonesia have not yet fully found a way to anticipate the impact of lower policy interest rates on their profitability. Meanwhile, BI7DRR only had a significant effect on NIM in the pre-pandemic period, considering that the decline in BI7DRR was not immediately responded to by banks by reducing credit interest rates.